Abdominal Distension Associated with Luminal Fungi in the Intestines of Axolotl Larvae. (12th May 2015) - Zullian, Chiara; Dodelet-Devillers, Aurore; Roy, Stéphane; Hélie, Pierre; Vachon, Pascal
Abstract : Axolotls show a remarkable regeneration capacity compared with higher vertebrates, regenerating missing appendages such as limbs and tail as well as other body parts (i.e., apex of the heart, forebrain, and jaw) after amputations which makes this animal a very interesting research model for tissue regeneration mechanisms. Larvae are individually housed in a 20% Holtfreter's solution within clear plastic containers. The photoperiod light : darkness cycle is 12 : 12 h. Larvae with a total body length of less than 5 cm are fed once a day with large brine shrimp and blood worm. Albino larvae appeared to have a tendency to exhibit abdominal distention. No clinical signs of illness seemed to be associated with the condition; however, these animals exhibit a relatively slower growth rate. To better characterize this condition, we performed histological sectioning for cross sectional slide preparation on wild type and albino axolotl larvae following euthanasia. The only lesion seen in the albino larvae was a thickened gut wall and the presence of fungi within the intestines. We hypothesize that this may be due to a lower efficacy of the albino larvae's immune system.